Gambaran Tingkat Pengetahuan Masyarakat dalam Mengantisipasi Penyalit Pasca Banjir di RT 04, Dusun Nusupan, Desa Kadokan - Apriliyana, Putri; Silvitasari, Ika (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Floods occur when normally dry land areas are inundated with large volumes of water, generally caused by prolonged heavy rainfall or water runoff from higher areas. Following floods, the risk of infectious diseases increases due to the presence of infectious agents such as bacteria, viruses, parasites, and other hazardous substances. Common post-flood diseases include acute respiratory infections (ARI), diarrhea, typhoid fever, leptospirosis, dengue hemorrhagic fever (DHF), and skin diseases. This study aims to describe the characteristics of the community and their level of knowledge regarding efforts to prevent post-flood diseases in Dusun Nusupan. The research employed a descriptive quantitative method with purposive sampling, involving 67 respondents. Data were collected using questionnaires. The results showed that the majority of respondents were in late adulthood, female, had a middle-level education, and most had previously experienced post-flood diseases. The community’s level of knowledge was generally good, with nearly all respondents demonstrating adequate understanding of preventive measures. However, the high incidence of post-flood diseases among respondents highlights that public health risks remain significant. These findings indicate the necessity of continuous education and the implementation of clean and healthy living behaviors to minimize the health impacts of floods.